Pengaruh Literasi Keuangan, Financial Self Efficacy, dan Lifestyle terhadap Pengelolaan Keuangan Pribadi Mahasiswa/I Akuntansi - Pradisa, Riska; Amelia Tirana Sita; Elfin Krisdayanti Hia; Fachruli Hayu Biyantarimelia; Dian Widiyati (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study examines how to make lifestyle, financial literacy, and financial self-efficacy influence the personal financial management of accounting students in 2025. The research employs a quantitative approach using multiple linear regression analysis with a sample of 100 respondents. Data were gathered through a survey and analyzed using SPSS 25. The findings reveal that financial literacy (X1), financial self-efficacy (X2), and lifestyle (X3) collectively contribute to students’ financial management behavior. However, although financial self-efficacy shows a positive direction, its effect is not statistically significant. In contrast, financial literacy and lifestyle demonstrate significant impacts on how students manage their money. These results suggest that students who possess stronger financial knowledge and adopt responsible lifestyle patterns tend to demonstrate better personal financial planning, budgeting, saving, and spending habits. Overall, the study emphasizes the importance of educational institutions strengthening students’ financial literacy and encouraging healthy financial habits to prepare them for future financial independence.